1997
DOI: 10.1021/jo9702599
|View full text |Cite
|
Sign up to set email alerts
|

Diels−Alder Reaction of 2-Amino-Substituted Furans as a Method for Preparing Substituted Anilines

Abstract: 5-Amino-2-furancarboxylic acid methyl ester undergoes a facile Diels−Alder cycloaddition with a variety of dienophiles to afford ring-opened cycloadducts that are readily dehydrated using BF3· OEt2 to give polysubstituted anilines. In each case, the cycloaddition proceeds with high regioselectivity, with the electron-withdrawing group being located ortho to the amino group. The most favorable FMO interaction is between the HOMO of the furanamine and the LUMO of the dienophile. The atomic coefficient at the est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 44 publications
(64 reference statements)
2
76
0
Order By: Relevance
“…The overall yield of this approach was very low (13%), which was mostly due to the poor conversion of 17 to 18 in the first reaction step. The title 2,4-disubstituted aniline 12i was therefore synthesised using a different approach, starting from commercially available methyl 2-amino-5-furoate (20) and methyl acrylate, following a literature procedure [40]. After DielseAlder reaction in the first step the aminosubstituted 7-oxabicyclo[2.2.1]heptene 21 was spontaneously converted to substituted aniline 22.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…The overall yield of this approach was very low (13%), which was mostly due to the poor conversion of 17 to 18 in the first reaction step. The title 2,4-disubstituted aniline 12i was therefore synthesised using a different approach, starting from commercially available methyl 2-amino-5-furoate (20) and methyl acrylate, following a literature procedure [40]. After DielseAlder reaction in the first step the aminosubstituted 7-oxabicyclo[2.2.1]heptene 21 was spontaneously converted to substituted aniline 22.…”
Section: Chemistrymentioning
confidence: 99%
“…Method 1. Dimethyl 4-aminoisophthalate (12i) [40]. To a solution of compound 19 (300 mg, 1.00 mmol) in MeOH (15 mL), 10% Pd-C (30 mg) was added, and the mixture was hydrogenated for 10 h at room temperature.…”
Section: Synthesis Of Dimethyl 4-aminoisophthalate (12i)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ab initio molecular-orbital studies suggest that the presence of an amino group on the furan ring has a destabilizing effect on the aromaticity of furan [16] , as well as producing an increase in HOMO energy levels [12] . Both effects contribute to an increase in reactivity towards pericyclic reactions and promote exclusive selectivity in regiochemical outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…N-3'-furylbenzamide and 3-methylthiofuran [7,8] undergo facile cycloaddition with monoactivated dienophiles, and Schlessinger et al have demonstrated the preparation of oxabicycloheptanone adducts from chiral 3-furylamines for the construction of (+)-cyclophellitol [9,10] . 2-Aminofurans have also been prepared by Padwa et al and used in the preparation of substituted anilines and phenols [11,12] .…”
Section: Introductionmentioning
confidence: 99%